Photoelectrochemical Determination of Cardiac Troponin I as a Biomarker of Myocardial Infarction Using a Bi2S3 Film Electrodeposited on a BiVO4-Coated Fluorine-Doped Tin Oxide Electrode - Thatyara Oliveira Monteiro; Antônio Gomes dos Santos Neto; Alan Silva de Menezes; Flávio Santos Damos; Rita de Cássia Silva Luz; Orlando Fatibello-Filho (Biosensors, 2023)
A sensitive and selective label-free photoelectrochemical (PEC) immunosensor was designed for the detection of cardiac troponin I (cTnI). The platform was based on a fluorine-doped tin oxide (FTO)-coated glass photoelectrode modified with bismuth vanadate (BiVO4) and sensitized by an electrodeposited bismuth sulfide (Bi2S3) film. The PEC response of the Bi2S3/BiVO4/FTO platform for the ascorbic acid (AA) donor molecule was approximately 1.6-fold higher than the response observed in the absence of Bi2S3. The cTnI antibodies (anti-cTnI) were immobilized on the Bi2S3/BiVO4/FTO platform surface to produce the anti-cTnI/Bi2S3/BiVO4/FTO immunosensor, which was incubated in cTnI solution to inhibit the AA photocurrent. The photocurrent obtained by the proposed immunosensor presented a linear relationship with the logarithm of the cTnI concentration, ranging from 1 pg mL−1 to 1000 ng mL−1. The immunosensor was successfully employed in artificial blood plasma samples for the detection of cTnI, with recovery values ranging from 98.0% to 98.5%.